2004
DOI: 10.1088/0022-3727/37/9/002
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotransport study of nanoscale Permalloy–Si tunnelling structures in lateral spin-valve geometry

Abstract: Magnetotransport measurements were performed on a Permalloy/Mg/SiO 2 /n + -Si (100) spin-valve tunnelling device. Magnetic force microscope imaging proves the single-domain state of the 1 µm elongated and 200 nm wide parallel Permalloy (Py) electrodes. Anisotropic magnetoresistance (AMR) measurements reveal precisely the magnetic field interval of antiparallel magnetization configuration essential for spin-valve operation, in between the switching fields of 15 and 40 mT. Unlike the negative AMR of the Py wires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…1 In such a Co-Si heterostructure any structural disorder at the interface would drastically reduce the spin polarization, and hence the spin injection efficiency. [2][3][4] The phenomena observed at the initial stages of Co deposition on a Si substrate seem to be unique and depend on the preparation conditions. 5-10 About the growth mode of Co on Si, Cho et al 5 concluded that the Co atoms grow in a layer-by-layer mode, without any interdiffusion, whereas Meyerheim et al 6 and Rangelov et al 7 could see the in-diffusion of Co atoms for coverages higher than 0.5 ML of Co. About the atomic positions of Co atoms on Si ͑100͒, Scheuch et al, 8 Meyerheim et al, 6 and Gomoyunova et al 9 found that Co is adsorbed in fourfold hollow sites ͑nearly in plane, d Ќ Ϸ 0͒ in every second ͓110͔ row of the Si ͑100͒ surface.…”
mentioning
confidence: 99%
“…1 In such a Co-Si heterostructure any structural disorder at the interface would drastically reduce the spin polarization, and hence the spin injection efficiency. [2][3][4] The phenomena observed at the initial stages of Co deposition on a Si substrate seem to be unique and depend on the preparation conditions. 5-10 About the growth mode of Co on Si, Cho et al 5 concluded that the Co atoms grow in a layer-by-layer mode, without any interdiffusion, whereas Meyerheim et al 6 and Rangelov et al 7 could see the in-diffusion of Co atoms for coverages higher than 0.5 ML of Co. About the atomic positions of Co atoms on Si ͑100͒, Scheuch et al, 8 Meyerheim et al, 6 and Gomoyunova et al 9 found that Co is adsorbed in fourfold hollow sites ͑nearly in plane, d Ќ Ϸ 0͒ in every second ͓110͔ row of the Si ͑100͒ surface.…”
mentioning
confidence: 99%
“…1 (b) for a false-colour electron micrograph of a sample at this fabrication stage. A thin Py layer together with the negligible crystal anisotropy of Py favours a homogeneous in-plane magnetization aligned with the external magnetic field H 31,32 . The length of the spin transport channel L is defined by the Py and the Pt electrode separation.…”
Section: Working Principlementioning
confidence: 99%
“…Owing to its apparent advantages over other semiconductors, many groups tried to demonstrate phenomena attributed to spin transport in Si [31][32][33][34][35][36][37][38][39], but this was typically done with ohmic FM-Si contacts and two-terminal magnetoresistance measurements or in transistor-type devices [40,41], which are bound to fail owing to the 'fundamental obstacle' for ohmic spin injection mentioned in §1 [1][2][3][4]. Although weak spin-valve effects are often presented, no evidence of spin precession is available so the signals measured are ambiguous at best [42,43].…”
Section: Spins In Siliconmentioning
confidence: 99%